Cash on delivery or online payment: mobile channel, order size and payment methods. Issue 2 (4th June 2020) - Wu, Banggang; Deng, Xiaoyu; Cui, Xuebin
Abstract : Purpose: The existing research does not systematically explore customers' option about different payment methods, nor does it analyze how shopping channels and shopping scale affect customers' option about different payment methods. Furthermore, there is a lack of exploration on what the relationship is, and how they are adjusted by customer purchasing experience. The authors' research questions are: (1) when using different shopping channels in online retailing, whether customers will choose different types of payment methods? (2) Does the purchase amounts affect customers' choice of different payment methods? Design/methodology/approach: This study takes 60, 484 customers from JD.com, one of the largest B2C platforms in China, as the research object and collects the purchase data of these customers from October 01, 2012 to December 31, 2013, and analyzes them through panel data models. Findings: Based on their purchase data, the authors find the main results by using panel data model that (1) the use of mobile channel has a positive effect on cash on delivery (COD), implying that when consumers use mobile to purchase, they have a higher possibility to use COD, (2) the order size has a positive effects on COD, that is to say, when the purchase amount increases, the possibility of using COD also increases. (3) Furthermore, when consumers' purchase experience abound, mobile channel's positive effect on COD will be decreased, but it does not affect the positive effect between order size and COD. Originality/value: From the aspects of shopping channels, product attributes and customer purchase experience, it fills the gaps in the research on the preselection of payment methods and makes research of payment methods a complete research system. Secondly, this study adds COD to the options of payment method selection. Finally, the moderating effect of customer shopping experience from a dynamic perspective elaborates that customers can learn from multiple purchases and overcome the shopping risks brought by shopping channels, thereby reducing the probability of choosing a COD method.